FEMINISME DALAM SATUA NI TUWUNG KUNING - Komang Wahyu Rustiani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The discourse on women's emancipation essentially refers to two concepts of struggle, is name the physical and psychological struggle between the struggle of the world of reality and the world of ideas and ideas in the form of fiction. The movement to liberate Adam's power over women was marked by the emergence of women's groups or organizations in the west to Indonesia, then through a literary approach, the birth of literary works and even women writers to voice their rights to freedom of expression without any shadow of legitimacy. man. Especially in Bali, the presence of women's work is very helpful in efforts to polarize women's duties and functions in life. The balance of life has basically been formulated in the process of creating past living things by God Almighty, for the purpose of social survival. The culture of the colonialist education system has taught people to think broadly in addressing the existence of women. Even male writers have implicitly acknowledged the existence of women through the work of the Balinese unit, Satua Ni tuwung Kuning.Feminist literary criticism is a response from academics regarding gender interrelation. Emphasis on trichotomy, social, political and economic. Sociologically, the yellow Ni Tuwung unit reflects the traditional feminism movement and even presents a mythological figure, namely an angel (widiadari) as a symbol of the strength of the woman herself..Keyword: Feminism, Satua, and Ni Tuwung Kuning